Using the Temporal Versions Model in a Software Configuration Management Environment - Silva, Fabrício Ávila da; Costa, Raquel Vieira Coelho; Edelweiss, Nina; Santos, Clesio Saraiva dos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2003)
Temporal Versions Model (TVM) is an object-oriented data model with versioning facilities, allowing revisions and project alternatives, and temporal features, used to maintain the history of the system evolution. This paper presents TVM under a Software Configuration Management (SCM) perspective, compares this model with available SCM tools, and describes why TVM is adequate to be used as the basis of an SCM environment. A modeling example and the implementation of TVM on a commercial Database Management System (DBMS), which is an ongoing work, are also presented.